The Abstract Book of the 22nd European Conference on Development Psychology - Pakalniškienė, Vilmantė; Jusienė, Roma; Zamalijeva, Olga (Vilnius University Proceedings, 2026)
The European Conference on Developmental Psychology (ECDP) is the flagship biennial event organized by the European Association of Developmental Psychology (EADP). Serving as a premier hub for researchers, educators, and practitioners from across the globe, the conference is dedicated to advancing the scientific understanding of human development from infancy through adulthood. Researchers and practitioners gather to present cutting-edge empirical research, discuss innovative methodologies, and debate theoretical frameworks addressing critical contemporary issues, such as the impacts of digital technology on youth, socio-emotional development, and cognitive aging. The event fosters a vibrant, collaborative environment through a diverse program of keynote addresses from world-renowned experts, symposia, and interactive poster sessions. By prioritizing early-career researchers alongside established scholars, the ECDP plays a vital role in shaping the future of developmental science, promoting cross-cultural collaboration, and translating rigorous academic insights into impactful social policies and interventions worldwide. In collaboration with Vilnius University ECDP 2026 was hosted in Lithuania.